195k views
5 votes
F(x) = x2 + 1 g(x) = 5 – x

(f + g)(x) =

1 Answer

4 votes

Answer:


(f + g)(x) = {x}^(2) - x + 6

Explanation:

We have


f(x) = {x}^(2) + 1

and


g(x) = 5 - x

We want to find (f+g)(x).

By the algebraic properties of polynomial functions,


(f + g)(x) = f(x) + g(x)


(f + g)(x) = {x}^(2) + 1 + 5 - x

This simplifies to


(f + g)(x) = {x}^(2) - x + 6

We can't simplify further, hence the simplest form

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.